Method for synthesizing silicon oxide nanostructures with different morphologies by utilizing interaction of droplet growth and shell coating
By adjusting the solvent ratio, the amount of sodium citrate ammonia solution, and the number of seeds in a colloidal solution, the droplet growth rate can be controlled, and various morphologies of silica nanostructures can be synthesized. This solves the problem of complex synthesis of asymmetric structures in existing technologies, and enables simple and efficient mass production and widespread application.
Patent Information
- Application Number
- CN202410616486.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-17
- Publication Date
- 2025-11-18
AI Technical Summary
Existing technologies struggle to efficiently synthesize asymmetric silica nanostructures with various morphologies, and the synthesis process is cumbersome, time-consuming, and lacks a clear underlying principles.
By utilizing the interaction between droplet growth and silica shell coating in colloidal solution, the droplet growth rate was controlled by adjusting the solvent ratio, the amount of sodium citrate ammonia solution added, and the number of seeds, thus synthesizing silica nanostructures with different morphologies.
It has achieved continuous transformation of silica nanostructures from spherical to teardrop, bottle-shaped and bullet-shaped in the same system. The operation is simple, can be mass-produced, and is suitable for catalysis, biomedicine and adsorption fields.
Smart Images

Figure CN120964829A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technology of synthesizing silicon oxide with different morphologies directly in colloidal solution. Silicon oxide is a material with high stability and biocompatibility, so the above-mentioned structure can be applied to the fields of catalysis, biomedical, adsorption, etc. BACKGROUND
[0002] Definition of asymmetric structure: Asymmetric nanostructure refers to a nanoscale material or structure with non-symmetrical shape or composition. This asymmetry may involve differences in shape, chemical composition, surface properties, etc. Generally, asymmetric nanostructures have unique properties and applications because they can provide specific functions under specific conditions, such as enhancing the mechanical properties of materials, improving catalytic activity, regulating optical properties, etc.
[0003] Asymmetric structure: Compared with traditional symmetric structure, asymmetric structure has some unique advantages. For example, multifunctionality (containing several different properties at the same time), larger effective surface area and more active sites, and stronger synergistic effect (different regions of asymmetric structure can work independently without interfering with each other, or even cooperate with each other, thus significantly improving the performance of the structure). For example, the multi-chamber structure further synthesized based on asymmetric structure allows the establishment of multifunctional partition in different chambers and enables multiple biochemical reactions to occur without interfering with each other, which is crucial for expanding the application prospects of nanoparticles in the fields of nanoreactor, catalysis, and drug delivery. For example, a 2011 article prepared bullet-shaped asymmetric silica nanomaterials with adjustable length using a mixture of pentanol and water as solvent. They can form liquid crystal phase and isotropic and nematic phase, making them unique and very suitable as model systems for real-space studies of colloidal liquid crystals (J. Am. Chem. Soc. 2011, 133, 8, 2346-2349). A 2016 article introduced the synthesis of high-strength silica nanowires using two precursors, octadecyltrimethoxysilane and TBOS, in an emulsion system. The nanowires can be used as building blocks for constructing a new type of three-dimensional porous network of superhydrophobic functional materials. The constructed silica film has a superhydrophobic surface (water contact angle greater than 150°) and can be used as an adsorbent for oil / water separation (Angewandte Chemie International Edition, 2016, 55(29): 8375-8380.). A 2022 article proposed a nanodroplet reconstitution strategy for the synthesis of hierarchical multi-chamber mesoporous silica nanoparticles with adjustable chamber number (single-chamber to three-chamber nanostructure). This nanodroplet reconstitution strategy can promote the selective assembly of functional units (Fe3O4, Pd, Pt, etc.) in multi-chamber nanoparticles. The authors constructed a double-chamber nanoreactor with Au nanocrystals riveted in the first chamber and Pd nanocrystals anchored in the second chamber, which was used for the cascade reaction of 1-nitro-2-(phenylethynyl) benzene to synthesize 2-phenylindole. Due to the different spatial distribution of catalytically active centers, the double-chamber nanoreactor showed good catalytic performance in the cascade reaction to synthesize 2-phenylindole, with a selectivity of up to 76.5%, which was 1.85 times (about 41.3%) that of the single-chamber nanoreactor. Simulation results showed that the double-chamber structure can ensure efficient mass transfer of reactants and intermediates, thus facilitating the improvement of selectivity for 2-phenylindole product (Nature Communications 2022, 3, number: 6136). Asymmetric structure has very wide application prospects, but the above methods are relatively limited and can only synthesize a single specific structure, which is not universal. Secondly, some of the methods involve relatively complicated and time-consuming steps and the underlying synthesis principles are not clear. SUMMARY
[0004] The present application relates to a technology for synthesizing silicon oxide nanostructures with different morphologies directly in colloidal solution. Firstly, the technology is simple to operate and can be used for batch synthesis. Secondly, the synthesis conditions are mild, the stability is good, and the morphology is adjustable; the structure can be directly used for nano-reactors and drug carriers, and has strong practicality.
[0005] To solve the above technical problems, the technical solution proposed by the present application is: a method for preparing silicon oxide nanostructures with different morphologies by using the interaction of droplet growth and silicon oxide shell coating, characterized in that the method can be performed in the following steps in sequence:
[0006] (1) Thicken the mixed solution with a thickening agent, wherein the mixed solution is a mixed solution of ethanol and a low-polarity solvent (polarity range 0.06-2.4), and polyvinylpyrrolidone (PVP = 100 mg / ml) or polyethylene glycol (PEG = 4% (mass ratio to the mixed solution)) is used as the thickening agent of the mixed solution;
[0007] (2) Add an ammonia solution of sodium citrate to the solution in step (1) to induce phase separation and generate nanodroplets;
[0008] (3) Add tetraethyl orthosilicate (TEOS) in step (2) to nucleate and coat on the surface of the droplets, and by adjusting the relative rates of the two, silicon oxide structures with different morphologies can be obtained.
[0009] Preferably, the mixed solution in step 1 is a mixture of ethanol and a low-polarity solvent; the low-polarity solvent can be octanol, n-hexane, cyclohexane, or toluene. The high-molecular-weight thickening agent can be polyvinylpyrrolidone (PVP) or polyethylene glycol (PEG).
[0010] Preferably, the ratio of the mixed alcohol in step 1 can be adjusted to control the relative rates of droplet growth and silicon oxide shell coating, thereby synthesizing structures with different morphologies. If hollow spherical structures are needed, the ratio of ethanol to octanol in the mixed solution is 1:1; if tear-drop-shaped structures are needed, the ratio of ethanol to octanol in the mixed solution is 1:1.5; if bottle-shaped structures are needed, the ratio of ethanol to octanol in the mixed solution is 1:1.9; and if bullet-shaped structures are needed, the ratio of ethanol to octanol in the mixed solution is 1:5.7.
[0011] Preferably, the volume of the aqueous solution added in step 2 can control the relative rate of droplet growth and silica shell coating to synthesize structures with different morphologies. If hollow sphere structure is needed, the volume of the mixed solution of sodium citrate and ammonia solution added is 20 μL; if tear drop structure is needed, the volume of the mixed solution of sodium citrate and ammonia solution added is 25 μL; if bottle structure is needed, the volume of the mixed solution of sodium citrate and ammonia solution added is 30 μL; if bullet structure is needed, the volume of the mixed solution of sodium citrate and ammonia solution added is 45 μL.
[0012] Preferably, step c changes the amount of seeds to adjust the growth rate of droplets, the volume ratio of the mixed solution of ethanol, octanol and ammonia solution is 10:40:1, then different amounts of seed solution are added, and finally TEOS is added; the preparation of seeds is mixing 25 μL of sodium hydroxide ethanol solution and 75 μL of citric acid ethanol solution, and then the mixture is washed and concentrated in 100 μL of ethanol to be 1 equivalent; step c changes the amount of seeds to adjust the growth rate of droplets; if hollow sphere structure is needed, the amount of seeds added in the mixed solution is 1 / 4 equivalent; if tear drop structure is needed, the amount of seeds added in the mixed solution is 1 / 32-1 / 4 equivalent; if tadpole structure is needed, the amount of seeds added in the mixed solution is 1 / 64 equivalent.
[0013] Preferably, step d manually adds pure water to adjust the growth rate of droplets to synthesize gourd structure; the volume and adding time of the second water determine the size of the second node and the distance between the two nodes; if the volume of the second node needs to be increased, the volume of the added water is increased; if the distance between the two nodes needs to be increased, the time of the second water adding is prolonged, and vice versa.
[0014] Preferably, step d manually adds pure water to adjust the growth rate of droplets to synthesize gourd structure; whether 4-(chloromethyl)phenyl trimethoxysilane is added in step (3) will affect the morphology of the structure; when 4-(chloromethyl)phenyl trimethoxysilane is added, the second water growth will obtain a gourd with a cavity; when 4-(chloromethyl)phenyl trimethoxysilane is not added, the second water growth will obtain a gourd with a chamber.
[0015] To solve the above technical problems, another technical scheme of the present application is to use the interaction of droplet growth and silica shell coating to prepare silica nanostructures with different morphologies.
[0016] Advantages:
[0017] 1. This is a technology for preparing silica nanostructures with different morphologies by using the interaction of droplet growth and silica shell coating. The morphology of the structure can be adjusted from multiple parameters, and the structure with a specific morphology can be synthesized as needed for application.
[0018] 2. The morphology transformation of the structure in the present application can be realized by adjusting the droplet growth rate through the proportion of the solvent, and the continuous transformation of the structure from a spherical shape to a teardrop shape, a bottle, and then a bullet can be realized in the same system.
[0019] 3. The morphology transformation of the structure in the present application can be realized by adjusting the droplet growth rate through the proportion of the solvent, and the continuous transformation of the structure from a spherical shape to a teardrop shape, a bottle, and then a bullet can be realized in the same system.
[0020] 4. The morphology transformation of the structure in the present application can be realized by adjusting the droplet growth rate through the proportion of the solvent, and the continuous transformation of the structure from a spherical shape to a teardrop shape, a bottle, and then a bullet can be realized in the same system.
[0021] 5. The reaction solution has a certain robustness, the polymer thickening agent can be PVP or PEG, and the concentration of PVP can be adjusted within a certain range (25 mg / ml-100 mg / ml). The low-polarity solvent can be octanol, n-hexane, cyclohexane, and toluene. In addition, the continuous transformation of the above-mentioned morphology can also be realized by using a single alcohol with different polarity (such as ethanol, propanol, butanol, pentanol, and octanol, etc.), and other low-polarity solvents can also be changed according to specific conditions.
[0022] 6. If a multi-chambered silicon oxide nanostructure is to be synthesized, a surface-active silane (such as 4-(chloromethyl)phenyltrimethoxysilane, octadecyltrimethoxysilane, etc.) can be introduced to improve the problem of chamber solidification.
[0023] 7. The obtained teardrop-shaped and bottle-shaped asymmetric structures conform to the fluid mechanics configuration, and have higher transmission efficiency in the fields of drug carrying and nanorobot.
[0024] 8. The present application can synthesize specific structures as needed, which can be open, closed, multi-chambered, solidified, and asymmetric, etc., to meet different application requirements.
[0025] 9. The core of the present application is to adjust the mutual action of the droplet growth rate and the silicon oxide coating rate.
[0026] 10. The obtained asymmetric structure can be further grown, such as the bottle-shaped nanostructure which can be further grown into a nanowire.
[0027] 11. The nanowire can be used as a special hydrophobic material to construct a unit for adsorption, filtration, etc., and has a broad application prospect.
[0028]
[0029] 11. The main purpose of the present application is to synthesize different silica nanostructures such as spheres, teardrops, bottles and bullets in one step directly in colloidal solution. The present application is simple to operate, can be mass-produced, and the product is uniform and controllable. Moreover, the target structure can be designed and synthesized according to specific needs.
[0030] 12. We believe that changing the solution polarity and increasing the volume of sodium citrate aqueous ammonia solution both achieve the continuous transition of spherical, teardrop, bottle and bullet structures by increasing the growth rate of droplets. Increasing the proportion of octanol (reducing the polarity of the solution) will reduce the mutual solubility of the organic solution to water, so that there is more water for droplet growth;
[0031] Increasing the volume of sodium citrate aqueous ammonia solution, that is, increasing the water content in the solution, will also provide more water for droplet growth. In the water addition experiment again; the large amount of pure water added will cause the droplet growth rate to increase rapidly, the volume of the side not covered by the silica shell will expand rapidly, and the silica shell will continue to cover along the liquid surface to form a cavity. In the experiment of adjusting the seed concentration, the change in morphology is achieved by controlling the distribution of growth materials (water); under the condition of a very high number of seeds, the average amount of growth material (water) allocated to each seed is very small, which is difficult to support its asymmetric growth; eventually, hollow sphere structures will be obtained. When the number of seeds is very small, the average amount of growth material (water) allocated to each seed is large, which can support its growth for a longer period of time, and eventually a tadpole-like structure is obtained. BRIEF DESCRIPTION OF DRAWINGS
[0032] Figure 1 The morphology transition is controlled by adjusting the volume and polarity of the aqueous solution. When the volume of the aqueous solution is constant (40 μl), the TEM and SEM images of the products are shown in a-f, with the ethanol / octanol ratio (v / v) being 1:1, 1:1.5, 1:1.9, 1:2.3, 1:4 and 1:5.7, respectively; when the solution polarity is constant (the ethanol / octanol ratio (v / v) is 1:4), the TEM and SEM images of the products are shown in g, e, h-k, with the volume of the sodium citrate aqueous ammonia solution being 45 μl, 40 μl, 35 μl, 30 μl, 25 μl and 20 μl, respectively.
[0033] Figure 2 Single different polarity alcohol as solvent. a-e TEM images of products with ethanol, propanol, butanol, pentanol and octanol as solvents instead of ethanol / octanol mixture.
[0034] Figure 3 Universal of thickening agent and solvent. a TEM image of product with PEG as thickening agent. b-d TEM images of products with ethanol / cyclohexane (v / v) = 1:4, ethanol / n-hexane (v / v) = 1:4 and ethanol / toluene (v / v) = 1:15.
[0035] Figure 4 The morphology transition was controlled by adjusting the amount of seeds. TEM and SEM images of the products with the amount of seeds equivalent to 1 / 32, 1 / 16, 1 / 8 and 1 / 4 of the total amount were added, respectively.
[0036] Figure 5 Adjusting the nanobottle cavity. TEM images of cucumbers with different neck lengths after secondary growth. d-f TEM images of the secondary growth products of 35, 40, 45 μL of siloxane with only orthosilica.
[0037] Figure 6 is a schematic diagram of droplet growth and silica shell coating, in which the interaction of droplet growth rate (V E ) and silica shell coating rate (V P ) determines the geometry of the product. DETAILED DESCRIPTION
[0038] Example 1:
[0039] A method for preparing different morphologies of silica nanostructures by utilizing the interaction of droplet growth and silica shell coating, which can be carried out in the following steps in order:
[0040] (1) Thicken 1 mL of mixed alcohol (ethanol / octanol) with a thickening agent, i.e. the reaction system is a mixed solution thickened by polyvinylpyrrolidone (PVP) (100 mg / ml);
[0041] (2) Add 40 ul of sodium citrate (0.2 M) ammonia (6 M) solution to the solution in step (1) to induce phase separation and produce nanodroplets;
[0042] (3) Add 10 ul of tetraethyl orthosilicate (TEOS) in step (2) to make silica nucleate and gradually coat on the surface of the droplets.
[0043] Figure 1 a-e in FIG. 1 are TEM and SEM images of the products when the ethanol / octanol ratio (v / v) in step (1) is 1:1, 1:1.5, 1:1.9, 1:2.3, 1:4 and 1:5.7, respectively. As can be seen from the above figure, with the decrease of the polarity of the solution, the asymmetry of the structure becomes more and more obvious, and the structure changes from spherical to teardrop, bottle and bullet.
[0044] The change of solution polarity in step a adjusts the growth rate of the droplets; if hollow sphere structure is needed, the volume ratio of ethanol to octanol in the mixed solution is 1:1, if tear drop structure is needed, the volume ratio of ethanol to octanol in the mixed solution is 1:1.5, if bottle structure is needed, the volume ratio of ethanol to octanol in the mixed solution is 1:1.9, and if bullet structure is needed, the volume ratio of ethanol to octanol in the mixed solution is 1:5.7.
[0045] Example 2
[0046] A method for preparing different morphology silica nanostructures by utilizing the interaction of droplet growth and silica shell coating, which can be carried out in the following steps in order:
[0047] (1) 1 mL of mixed alcohol (ethanol / octanol (v / v) = 1:4) is thickened with a thickening agent, i.e. the reaction system is a mixed solution thickened with polyvinylpyrrolidone (PVP) (100 mg / ml);
[0048] (2) different volumes of sodium citrate (0.2 M) ammonia (6 M) solution are added to the solution in step (1) to induce phase separation to produce nanodroplets;
[0049] (3) 10 ul of tetraethyl orthosilicate (TEOS) is added in step (2) to make silica nucleate and gradually coat on the surface of the droplets.
[0050] Figure 1 The TEM and SEM images of the products in g, e and h-k in step (2) are added with 45, 40, 35, 30, 25 and 20 μL of sodium citrate ammonia solution. As can be seen from the above figure, with the increase of the content of sodium citrate ammonia solution, the asymmetry of the structure is more and more obvious, and the structure changes from spherical to tear drop, bottle and bullet.
[0051] The change of the content of sodium citrate ammonia solution in the solution adjusts the growth rate of the droplets; if hollow sphere structure is needed, the added volume of sodium citrate ammonia solution in the mixed solution is 20 μL, if tear drop structure is needed, the added volume of sodium citrate ammonia solution in the mixed solution is 25 μL, if bottle structure is needed, the added volume of sodium citrate ammonia solution in the mixed solution is 30 μL, and if bullet structure is needed, the added volume of sodium citrate ammonia solution in the mixed solution is 45 μL.
[0052] Example 3
[0053] A method for preparing different morphology silica nanostructures by utilizing the interaction of droplet growth and silica shell coating, which can be carried out in the following steps in order:
[0054] (1) 1 ml of a single alcohol (a single alcohol with different polarity) is thickened with a thickening agent, i.e. the reaction system is a polyvinylpyrrolidone (PVP) thickened (100 mg / ml) mixed solution;
[0055] (2) 40 ul of a sodium citrate (0.2 M) ammonia water (6 M) solution is added to the solution in step (1) to induce phase separation to produce nanodroplets;
[0056] (3) 10 ul of tetraethyl orthosilicate (TEOS) is added in step (2) to make silica nucleate and gradually coat on the surface of the droplets.
[0057] Figure 2 a-e in FIG. 1 are TEM images of the products in step (1) using ethanol, propanol, butanol, pentanol and octanol as solvents instead of ethanol / octanol mixed alcohol, respectively. As can be seen from the above figure, with the decrease of the polarity of the solution, the asymmetry of the structure becomes more and more obvious, and the structure changes from spherical to teardrop-shaped, bottle-shaped and bullet-shaped.
[0058] Example 4:
[0059] A method for preparing different morphologies of silica nanostructures by the interaction of droplet growth and silica shell coating, which can be carried out in the following steps in turn:
[0060] (1) 1 mL of a mixed solution (ethanol / low-polarity solvent) is thickened with a thickening agent, i.e. the reaction system is a high-molecular-weight thickened mixed solution;
[0061] (2) 30 ul of a sodium citrate (0.2 M) ammonia water (6 M) solution is added to the solution in step (1) to induce phase separation to produce nanodroplets;
[0062] (3) 10 ul of tetraethyl orthosilicate (TEOS) is added in step (2) to make silica nucleate and gradually coat on the surface of the droplets.
[0063] Figure 3 a in FIG. 2 is a TEM image of the product in step (1) using PEG (4% (mass ratio to mixed alcohol)) as a thickening agent. b-d are TEM images of the products in step (1) using ethanol / cyclohexane (v / v) = 1:4, ethanol / n-hexane (v / v) = 1:4 and ethanol / toluene (v / v) = 1:15, PVP (100 mg / ml) thickening. The above selection of ethanol / octanol pairs is not absolute, and different polar alcohols, such as n-propanol, n-butanol, n-pentanol and n-octanol, will also produce similar morphology changes after adjusting the solvent ratio. Furthermore, other low-polarity solvents, such as n-hexane, cyclohexane and toluene, can also replace octanol. The thickening agent PVP is intended to increase the viscosity of the solution and reduce the aggregation / coalescence of liquid nanoparticles. It can be replaced by polyethylene glycol, highlighting the universality of this synthesis method.
[0064] Example 5:
[0065] A method for preparing different morphology silica nanostructures by the interaction of droplet growth and silica shell coating, which can be carried out in the following steps in turn:
[0066] (1) 1 mL of mixed alcohol (ethanol / octanol (v / v) = 1:4) is thickened with a thickening agent, i.e. the reaction system is a mixed solution thickened by polyvinylpyrrolidone (PVP) (100 mg / ml);
[0067] (2) 20 ul of ammonia (6M) solution is added to the solution in step (1) to induce phase separation to produce nanodroplets;
[0068] (3) 10 ul of tetraethyl orthosilicate (TEOS) is added in step (2) to make silica nucleate and gradually coat on the surface of the droplets.
[0069] Figure 4 a-d in the above table are adjusted by adjusting the amount of seeds to control the morphology transition. The preparation of seeds is to mix 25 μL of sodium hydroxide ethanol solution and 75 μL of citric acid ethanol solution, and then wash and concentrate them in 100 μL of ethanol, which is recorded as 1 equivalent. In step (2), 1 / 32, 1 / 16, 1 / 8 and 1 / 4 equivalent of seed product are added respectively, and TEM and SEM images are shown in the above table. As can be seen from the above table, with the decrease of the number of seeds, the asymmetry of the structure becomes more and more obvious, and the structure changes from spherical to teardrop-shaped and tadpole-shaped.
[0070] The amount of seeds added in the mixed solution is adjusted to adjust the growth rate of the droplets; if hollow sphere structure is needed, the amount of seeds added in the mixed solution is 1 / 4 equivalent, if teardrop structure is needed, the amount of seeds added in the mixed solution is 1 / 32-1 / 4 equivalent, and if tadpole structure is needed, the amount of seeds added in the mixed solution is 1 / 64 equivalent.
[0071] Example 6:
[0072] A method for preparing different morphology silica nanostructures by the interaction of droplet growth and silica shell coating, which can be carried out in the following steps in turn:
[0073] (1) 1 mL of mixed alcohol (ethanol / octanol (v / v) = 1:4) is thickened with a thickening agent, i.e. the reaction system is a mixed solution thickened by polyvinylpyrrolidone (PVP) (100 mg / ml);
[0074] (2) 30 ul of ammonia (6M) solution is added to the solution in step (1) to induce phase separation to produce nanodroplets;
[0075] (3) In step (2), 10ul of tetraethyl orthosilicate (TEOS) and 1ul of 4-(chloromethyl)phenyltrimethoxysilane were added to make the silica nucleate and gradually coat on the surface of the droplets.
[0076] (4) In step (3), water was added again after a period of time to obtain the second chamber by instantaneously increasing the growth rate of the droplets.
[0077] Figure 5 The TEM images of the gourds with different neck lengths after the water was added again (30ul of water was added) when the reaction in step (3) was carried out for 30min, 60min and 120min, respectively, are shown in a-c.
[0078] The addition of 4-(chloromethyl)phenyltrimethoxysilane in step (3) affects the morphology of the structure. When 4-(chloromethyl)phenyltrimethoxysilane is added, the gourd with a cavity is obtained after the water is added again. When 4-(chloromethyl)phenyltrimethoxysilane is not added, the gourd with a chamber is obtained after the water is added again.
[0079] Example 7:
[0080] A method for preparing silica nanostructures with different morphologies by using the interaction of droplet growth and silica shell coating, which can be carried out in the following steps in order:
[0081] (1) 1mL of mixed alcohol (ethanol / octanol (v / v) = 1:4) was thickened with a thickening agent, i.e. the reaction system was a mixed solution thickened with polyvinylpyrrolidone (PVP) (100mg / ml);
[0082] (2) 30ul of ammonia solution (6M) was added to the solution in step (1) to induce phase separation to produce nanodroplets;
[0083] (3) In step (2), 10ul of tetraethyl orthosilicate (TEOS) was added to make the silica nucleate and gradually coat on the surface of the droplets, and the reaction was carried out for 30min.
[0084] (4) After step (3), water was added again after a period of time to obtain the second chamber by instantaneously increasing the growth rate of the droplets.
[0085] Figure 5 The TEM images of the products after the water was added again after the reaction in step (3) was carried out for 30min, and 35ul, 40ul and 45ul of water were added, respectively, are shown in d-f. The gourd with a chamber was obtained. The volume and the addition time of the water added again determine the size of the second node and the distance between the two nodes. If the volume of the second node needs to be increased, the amount of the water added again should be increased. If the distance between the two nodes needs to be increased, the time of the water added again should be prolonged. Conversely, the same is true.
[0086] We explicitly show the competing factors behind the evolution of these nanostructures. The introduction of surfactant-like siloxanes has been shown to help overcome the solidification problem, paving the way for more complex asymmetric nanostructures. The present invention opens new possibilities for the synthesis of asymmetric nanostructures.
[0087] Finally, it needs to be emphasized that the concentration, volume, solvent ratio and other technical parameter content mentioned in the technical scheme of the invention can be adjusted, which is not limited by the actual parameters mentioned in this paper. In addition, the above specific description of the present invention is only used to illustrate the technical scheme of the present invention and is not limited to the specific examples described in the present invention. Those skilled in the art should understand that any modification or equivalent replacement of the present invention to achieve the same technical effect is within the scope of the present invention.
Claims
1. A method for preparing silica nanostructures with different morphologies by utilizing the interaction between droplet growth and silica shell coating, characterized in that: Includes the following steps: (1) The mixed solution is thickened with a thickener, wherein the mixed solution is a mixture of ethanol and a low polarity solvent (polarity range 0.06 to 2.4), and the thickener is polyvinylpyrrolidone or polyethylene glycol; (2) Add an ammonia solution of sodium citrate to the solution in step (1) to induce phase separation and generate nanodroplets; (3) Add tetraethyl orthosilicate (TEOS) in step (2) to nucleate and coat the droplet surface; Different morphologies of silicon oxide structures can be synthesized through any of the following methods and steps: a. Adjusting the growth rate of droplets by changing the polarity of the solution: In step (1), the ratio of ethanol and low-polarity solvent in the mixed solution is changed to adjust the growth rate of droplets, thereby achieving the synthesis of multimorphic structures. b. Adjust the droplet growth rate by changing the content of sodium citrate ammonia solution in the solution. In step (2), gradually increase the amount of sodium citrate ammonia solution added to achieve the synthesis of multimorphic structures. c. Adjust the growth rate of droplets by changing the number of seeds. In step (2), the seed solution is used instead of sodium citrate. The number of seeds in the solution is gradually reduced so that each seed can be allocated more growth material to achieve the synthesis of multimorphic structures. d. Manually add water to adjust the growth rate of the droplets. In step (3), add or do not add 4-(chloromethyl)phenyltrimethoxysilane. At certain intervals of 30, 60, and 120 min, add a certain volume of pure water (30-45 μL) to accelerate the growth rate of the droplets, thereby achieving the synthesis of the gourd structure.
2. The method for preparing silicon oxide nanostructures with different morphologies by utilizing the interaction between droplet growth and silicon oxide shell coating according to claim 1, characterized in that: The low-polarity solvent mentioned in step (1) is any one of octanol, n-hexane, cyclohexane, and toluene.
3. The method for preparing silicon oxide nanostructures with different morphologies by utilizing the interaction between droplet growth and silicon oxide shell coating according to claim 1, characterized in that: The polymer thickener mentioned in step (1) is polyvinylpyrrolidone (PVP = 100 mg / ml) or polyethylene glycol (PEG = 4%, by mass ratio to the mixed solution).
4. The method for preparing silicon oxide nanostructures with different morphologies by utilizing the interaction between droplet growth and silicon oxide shell coating according to claim 1, characterized in that: The low-polarity solvent mentioned in step a is octanol; the volume ratio of sodium citrate ammonia solution to the mixed solution is 1:25; the change of solution polarity in step a adjusts the droplet growth rate; if a hollow sphere structure is required, the volume ratio of ethanol to octanol in the mixed solution is 1:1; if a teardrop structure is required, the volume ratio of ethanol to octanol in the mixed solution is 1:1.5; if a bottle structure is required, the volume ratio of ethanol to octanol in the mixed solution is 1:1.9; if a bullet structure is required, the volume ratio of ethanol to octanol in the mixed solution is 1:5.
7.
5. The method for preparing silicon oxide nanostructures with different morphologies by utilizing the interaction between droplet growth and silicon oxide shell coating according to claim 1, characterized in that: Step b describes adjusting the droplet growth rate by changing the ammonia solution content of sodium citrate in the solution; the ratio of ethanol to octanol in the mixed solution is 1:4; if a hollow sphere structure is required, the volume of sodium citrate in ammonia solution added to 1 mL of the mixed solution is 20 μL; if a teardrop structure is required, the volume of sodium citrate in ammonia solution added to 1 mL of the mixed solution is 25 μL; if a bottle structure is required, the volume of sodium citrate in ammonia solution added to 1 mL of the mixed solution is 30 μL; and if a bullet structure is required, the volume of sodium citrate in ammonia solution added to 1 mL of the mixed solution is 45 μL.
6. The method for preparing silicon oxide nanostructures with different morphologies by utilizing the interaction between droplet growth and silicon oxide shell coating according to claim 1, characterized in that: Step c involves adjusting the droplet growth rate by changing the number of seeds. The volume ratio of ethanol, octanol, and ammonia solution in the mixed solution is 10:40:
1. Subsequently, different equivalents of seed solution are added, and finally TEOS is added. The seeds are prepared by mixing 25 μL of sodium hydroxide ethanol solution and 75 μL of citric acid ethanol solution, then washing and concentrating the mixture in 100 μL of ethanol, which is recorded as 1 equivalent. Step c describes adjusting the droplet growth rate by changing the number of seeds. If a hollow sphere structure is required, the amount of seeds added to the mixed solution is 1 / 4 equivalent; if a teardrop structure is required, the amount of seeds added to the mixed solution is 1 / 32 to 1 / 4 equivalent; and if a tadpole structure is required, the amount of seeds added to the mixed solution is 1 / 64 equivalent.
7. The method for preparing silicon oxide nanostructures with different morphologies by utilizing the interaction between droplet growth and silicon oxide shell coating according to claim 1, characterized in that: Step d involves manually adding pure water to adjust the growth rate of the droplets to synthesize the gourd structure; the volume and time of adding water again determine the size of the second node and the distance between the two nodes. If it is necessary to increase the volume of the second node, the volume of water added should be increased; if it is necessary to increase the distance between the two nodes, the time of adding water a second time should be extended, and vice versa.
8. The method for preparing silicon oxide nanostructures with different morphologies by utilizing the interaction between droplet growth and silicon oxide shell coating according to claim 1, characterized in that: In step d, pure water is manually added to adjust the growth rate of the droplets to synthesize the gourd structure; whether or not 4-(chloromethyl)phenyltrimethoxysilane is added in step (3) will affect the morphology of the structure. When 4-(chloromethyl)phenyltrimethoxysilane is added, water is added again to grow the gourd and the structure will be hollow. When 4-(chloromethyl)phenyltrimethoxysilane is not added, water is added again to grow the structure and the structure will be solidified.